Structural effect of principals change leadership on e-learning effectiveness - Laili Komariyah; Maulana Amirul Adha; Nova Syafira Ariyanti (International Journal of Evaluation and Research in Education (IJERE), 2024)
The aim of this research was to investigating the structural effect of the principal change leadership on the effectiveness of online-based learning with teacher work commitment and teacher attitudes towards change as mediator variables, which were approached quantitatively. Multilevel stratified proportional random sampling technique is used in sampling, while inclusion criteria are principals and teachers of primary schools who are still active in Kutai Kartanegara, Samarinda and Balikpapan, East Kalimantan, Indonesia. The structural equation modeling (SEM) analysis technique is used in this research. The results of the study show that the principals’ change leadership has a direct effect on the effectiveness of online-based learning, as well as an indirect effect through teacher work commitment and teacher attitudes towards change. This research contributes both theoretically and practically, where the change leadership demonstrated by the principal can ideally encourage teacher work commitment and teacher attitudes towards change, which in turn can promote the effectiveness of the implementation of online learning, as an effort to meet student learning needs.